(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents the results of sociological research to identify the state of physical education in the system of preschool educational institutions. 27 teachers of preschool educational institutions working with children of the older age group at the stage of their preparation for studying in the school education system took part in the survey.